Using Lead Concentrations and Stable Lead Isotope Ratios to Identify Contamination Events in Alluvial Soils - Diane Saint-Laurent; Julien St-Laurent; Marlies Hähni; Bassam Ghaleb; Camille Chapados (Applied and Environmental Soil Science)
Soils contaminated with hydrocarbons (C10–C50), polycyclic aromatic hydrocarbons (PAHs), and other contaminants (e.g., As, Cd, Cu, Pb) were recently discovered on the banks of the Saint-François and Massawippi rivers. Alluvial soils are contaminated over a distance of 100 kilometers, and the level of the contaminated-hydrocarbon layer in the soil profiles is among the highest at the Windsor and Richmond sites. Concentrations of lead and stable lead isotope ratios (204Pb/206Pb, 207Pb/206Pb, 208Pb/206Pb) are also used to identify contamination events. The maximum and minimum values detected in soil profiles for arsenic, cadmium, and lead vary from 3.01 to 37.88 mg kg-1 (As), 0.11 to 0.81 mg kg-1 (Cd) 12.32 to 149.13 mg kg-1 (Pb), respectively, while the 207Pb/206Pb isotopic ratio values are between 0.8545 and 0.8724 for all the profiles. The highest values of trace elements (As, Pb and Zn) were detected in the hydrocarbon layer (C10–C50), most often located at the bottom of the profiles (160, 200, and 220 cm in depth). The various peaks recorded in the soils and the position of the profiles suggest that various contaminants were transported by the river on several occasions and infiltrated the soil matrix or deposited on floodplains during successive floods. Atmospheric particles which entered the river or deposited on riverbanks must also be considered as another source of pollution recorded in soils.